37=29-2(x-1)

Simple and best practice solution for 37=29-2(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 37=29-2(x-1) equation:


Simplifying
37 = 29 + -2(x + -1)

Reorder the terms:
37 = 29 + -2(-1 + x)
37 = 29 + (-1 * -2 + x * -2)
37 = 29 + (2 + -2x)

Combine like terms: 29 + 2 = 31
37 = 31 + -2x

Solving
37 = 31 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
37 + 2x = 31 + -2x + 2x

Combine like terms: -2x + 2x = 0
37 + 2x = 31 + 0
37 + 2x = 31

Add '-37' to each side of the equation.
37 + -37 + 2x = 31 + -37

Combine like terms: 37 + -37 = 0
0 + 2x = 31 + -37
2x = 31 + -37

Combine like terms: 31 + -37 = -6
2x = -6

Divide each side by '2'.
x = -3

Simplifying
x = -3

See similar equations:

| 0.09xX=115.80 | | 8/50= | | w=8s+p | | -16+26=2(x+1) | | .75x+3=x+.5 | | 6/3x-5=3/2x | | 2(x-10)=-8 | | 0.09xX=83.07 | | (-4±√20)/2 | | -9-2x+6x=27 | | 37x+7=6(6x+1) | | 18x-7=14x-23 | | 2x+23y=11 | | y+1.2=2 | | 9x+1.5y=11 | | x+56=-24 | | -10z-0.9=-20z+1.1 | | -9+2+3x=22 | | 2(2x+2)+2(x+34)=312 | | 2x^2+30x+189=0 | | f(n)=9/n | | X/10-x/35=1/10 | | -5.39=logx | | 7x+2=5x+3 | | 6(79-5x)=11(4x-4) | | 180-x=.4(x)+5 | | 2(x+3)=8x-33 | | Y=10x^3+6 | | 13x-8y=-711 | | 8+2=-5(4x+2) | | 4(3x+9)=-32+44 | | 4(5x-2)=18 |

Equations solver categories